2018
DOI: 10.1111/jfs.12585
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, genotyping, serotyping, and antibiotic resistance of isolated Salmonella strains from industrial and local eggs in Iran

Abstract: This present study aimed to evaluate prevalence and characterization of serotypes, antimicrobial resistance (AMR) and genotypic profiles of Salmonella isolates in industrial and local eggs from Zanjan province of Iran. A total of 120 egg samples were collected and processed according to bacteriological analytical manual to isolate Salmonella strains from both eggs surface and contents. PCR method and genotyping were used to verify, identification and classification of isolates by screening invA genes and 16 s‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
11
3
Order By: Relevance
“…The prevalence of Salmonella in egg contents only was 2.22% which was similar to Taddese et al [20] stated that farms egg contents, and market egg contents with 2.4%, and 3.6% Salmonella was prevalent in Jimma Town, Ethiopia. However, the present study was higher than the findings of Karimiazar et al [25] reported that 1.66% of industrial and local egg contents contaminated with Salmonella in Zanjan province, Iran. Islam et al [18] stated that 7.14% of Salmonella prevalent in egg contents in Dhaka city, Bangladesh.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of Salmonella in egg contents only was 2.22% which was similar to Taddese et al [20] stated that farms egg contents, and market egg contents with 2.4%, and 3.6% Salmonella was prevalent in Jimma Town, Ethiopia. However, the present study was higher than the findings of Karimiazar et al [25] reported that 1.66% of industrial and local egg contents contaminated with Salmonella in Zanjan province, Iran. Islam et al [18] stated that 7.14% of Salmonella prevalent in egg contents in Dhaka city, Bangladesh.…”
Section: Discussioncontrasting
confidence: 92%
“…Islam et al [18] reported that 13.57% of eggshells contaminated with Salmonella in Dhaka city, Bangladesh. However, El-Kholy et al [24] and Karimiazar et al [25] found no contamination of Salmonella in examined eggshell samples.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 21 publications investigated antibiotic resistance in 1009 isolates from egg-laying hens farms and eggs from Asia (9 studies), Africa (7 studies), Europe (3 studies), and the Americas (2 studies) (Figure -5) [32,74,96,[163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180]. Most of the studies report the presence of Salmonella on eggshells (11 studies), followed by egg-laying hens (10 studies).…”
Section: Antibiotic Resistance In Eggs and Egg-laying Hens In The Worldmentioning
confidence: 99%
“…Ceftriaxone (CRO), ceftiofur (CEF), cefotaxime (CFT), ceftazidime (CAZ), cefoxitin (FOX), cefepime (CPE), cefazolin (CFZ); 7 carbapenems: Ertapenem (ETP), imipenem (IMP), meropenem (MER); 8 monobactams: Aztreonam (AZT)[32,74,96,[163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180].…”
mentioning
confidence: 99%
“…Taking into account the antibiotics used in other fields, Salmonella has developed high resistance to a broad range of antibiotics, leading to increased healthcare costs and clinical treatment failure ( Cui et al, 2016 ). Many studies have characterized Salmonella in poultry and poultry-associated foods globally, especially eggs ( Moffatt et al, 2017 ; Kouam et al, 2018 ; Li et al, 2018 ; FDA, 2019a , b , c ; Karimiazar et al, 2019 ; Kingsbury et al, 2019 ; Sanchez-Salazar et al, 2019 ). Evidence suggests that the genetic diversity of Salmonella isolated from various sources is abundant, whereas the isolates from the same poultry farms are closely related ( Xie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%